Molybdenum in treatment of broccoli seeds (Research, Society and Development, 2022)
Broccoli is a molybdenum-demanding crop, however, this nutrient is required in small amounts and perhaps the plants' needs can be met through seed treatments. However, this treatment cannot harm the physiological quality of the seeds. Thus, the objective of this work was to evaluate the effect of treatment with molybdenum in broccoli seeds on physiological quality. Eleven treatments were evaluated [factorial 2 sources (ammonium molybdate and molybdenum in the form of amino acid chelate) x 5 concentrations (0.5; 2.5; 5.0; 10.0; 25.0 g L-1 of water) + 1 untreated control] in a completely randomized design, with four replications. The treatment was done with the immersion of the seeds in the solutions/treatments for 30 minutes and then the seeds were dried. Germination, first germination count, germination speed index, electrical conductivity, emergence, emergence speed index and shoot dry weight were evaluated. Comparing the sources of molybdenum, the treatment with ammonium molybdate presented a higher value for the first germination count than the chelate. In general, there was a reduction in germination and vigor of seeds treated with molybdenum compared to control, especially at higher doses. Therefore, it is not recommended to treat broccoli seeds by the immersion method in the concentrations and sources tested.